Optimising CFRP strengthening for RC columns subject to axial compression and lateral impact: an experimental study - Almatrafi, Abdulrahman A.; Cunningham, Lee S.; Wu, Zhangjian (Innovative infrastructure solutions : the official journal of the Soil-Structure Interaction Group in Egypt (SSIGE), 2025)
In a typical frame building, columns can be vulnerable to impact arising from accidental actions such as vehicular collisions. Depending on the nature of the structure and its degree of robustness, failure of a column under impact may lead to progressive collapse. In the case of reinforced concrete (RC) frames, various options exist for strengthening existing columns against impact, including the use of externally bonded carbon fibre reinforced polymer (CFRP). Whilst the application of CFRP in static loading situations has been extensively investigated, comparatively little research has been undertaken on the use of this strengthening method for lateral impact situations. Importantly, for the case of square columns, the effect of the axial loading ratio on the strengthened column’s impact response has not been fully investigated, nor has the identification of optimum CFRP strengthening configurations. The present work details an experimental investigation in which nine RC square columns were tested under lateral impact and co-existing axial compression using a purpose-built test rig incorporating a drop hammer and disc spring pile. Axial compression ratios of 5%, 25% and 50% in relation to the theoretical axial capacity of the column as predicted by Eurocode 2 were investigated. Similarly, a number of practically driven CFRP configurations were examined with a view to the identification of optimum strengthening. The test series revealed the axial compression ratio to be inversely proportional to the lateral displacement resulting from impact. As an alternative to full wrapping of the column member, the use of discrete bands of CFRP was found to produce comparable levels of performance in terms of lateral displacement and crack limitation, whilst resulting in a ~ 40% saving in CFRP material. Both full wrapping and discrete banding achieved at least a 30% reduction in displacement compared to the corresponding un-strengthened member.